Study of the spectral response in the visible spectral region the ZnSe thin films (2014)
In this work are presented results in the study of photoconductivity of ZnSe thin films deposited on glass substrates at different temperatures, under high vacuum using thermal evaporation technique. The effect of substrate temperature on the spectral pho